THE EFFECTS OF APPROACH INSTRUCTION ON STUDENT’S READING PERFORMANCE - Umiyati Jabri; Kasdir kasdir; Elihami Elihami; Ibrahim Ibrahim (JURNAL EDUKASI NONFORMAL, 2019)
The research study investigated Indonesian EFL learners’ approach of two reading approaches (cognitive and metacognitive), their perceived contact on effectiveness, and the association between reading approach and effectiveness on their English reading comprehension. Fifty-Three English-major freshmen from STKIP Muhammadiyah of Enrekang participated in these lessons. Two principal questions namely: (1) what is the most frequent use of reading approach reported by individual students? (2) Is there any significant association between reading approach and effectiveness on their English reading comprehension? To examine the effects of approach instruction on students’ reading performance, a qualitative interview technique and quantitative research methods including a paired-sample t-test and Person Product Moment Correlation were used to estimate the relationship between reading approach use and effectiveness on students’ reading accomplishment. Significance showed that the most frequent use of reading approach was found to be metacognitive approach, followed by the cognitive approach. In addition, there was a significant positive connection between reading approach and effectiveness on their English reading comprehension. Reading approach, on the other hand, was unrelated to reading achievement. Results of interview findings were analyzed to explore in-depth in sequence about the condition of approach used. The implications of these findings for implementing effective reading strategy instruction are discussed.